2013
DOI: 10.1007/s00266-013-0111-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of Selective Serotonin Reuptake Inhibitors Antidepressants and Bleeding Risk in Breast Cosmetic Surgery

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…The studies, which vary in terms of methodology and types of surgery, include: seven orthopedic (3642), four coronary artery bypass grafting (CABG) (4346), one breast cancer (47), one breast cosmetic (48), one facelift (49), two postpartum (50,51), one dental, (52) one percutaneous endoscopic biopsy (53), and one large study of all in-hospital operative procedures (3). …”
Section: Ssris and Peri-operative Or Post-partum Bleedingmentioning
confidence: 99%
“…The studies, which vary in terms of methodology and types of surgery, include: seven orthopedic (3642), four coronary artery bypass grafting (CABG) (4346), one breast cancer (47), one breast cosmetic (48), one facelift (49), two postpartum (50,51), one dental, (52) one percutaneous endoscopic biopsy (53), and one large study of all in-hospital operative procedures (3). …”
Section: Ssris and Peri-operative Or Post-partum Bleedingmentioning
confidence: 99%
“…Furthermore, alcohol and other pharmacological agents may potentiate the effects of both ASA and non-ASA NSAIDs. [161][162][163][164][165][166][167][168][169][170] Summary Recommendations for Non-ASA NSAIDs…”
Section: Procedural Recommendations: Overviewmentioning
confidence: 99%
“…Patients using SSRIs had a 4-fold greater risk of breast hematoma formation requiring intervention compared with nonusers. 167 Serotonin reuptake inhibitor use was also associated with increased perioperative bleeding in orthopedic surgery. 170,386 In a retrospective follow-up study of 520 patients undergoing orthopedic surgery, the risk of intraoperative blood transfusion almost quadrupled in the SRI group compared with nonusers.…”
Section: Mechanisms Of Increased Bleeding Riskmentioning
confidence: 99%
“…Furthermore, alcohol and other pharmacological agents may potentiate the effects of both aspirin and non-aspirin NSAIDs. [145][146][147][148][149][150][151][152][153][154] For individuals taking aspirin for secondary prophylaxis who will be discontinuing aspirin while undergoing a spinal cord stimulator trial, it is recommended that the length of the trial be minimized. It is suggested that, for these patients, one considers a risk-benefit ratio for adequate trialing versus the possibility of cardiovascular sequelae.…”
Section: Procedural Recommendationsmentioning
confidence: 99%
“…Patients using SSRIs had a 4-fold greater risk of breast hematoma formation requiring intervention compared with nonusers. 151 The SRI use was also associated with increased perioperative bleeding in orthopedic surgery. 154,350 In a retrospective follow-up study of 520 patients undergoing orthopedic surgery, the risk of intraoperative blood transfusion almost quadrupled in the SRI group compared with nonusers [adjusted odds ratio (OR), 3.7; 95% CI, 1.4-10.2].…”
Section: Mechanisms Of Increased Bleeding Riskmentioning
confidence: 99%